2016
DOI: 10.1200/jgo.2015.001479
|View full text |Cite
|
Sign up to set email alerts
|

Significance of Magnetic Resonance Imaging–Assessed Tumor Response for Locally Advanced Rectal Cancer Treated With Preoperative Long-Course Chemoradiation

Abstract: PurposeTo study the predictive and prognostic value of magnetic resonance imaging (MRI)–assessed tumor response after long-course neoadjuvant therapy for locally advanced rectal cancer.MethodsThis study included 79 patients who had T3 or T4 and/or N+ rectal cancer treated with long-course neoadjuvant chemoradiation. MRI-assessed tumor regression grade (mrTRG) was assessed in 64 patients. MRIs were reviewed by the study radiologist. Surgical and pathologic reports for those who underwent surgery were reviewed. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…MR tumor regression grade (mrTRG) has been reported to be an excellent method for differentiating good from poor response in patients with rectal cancer [ 41 42 ]. Further studies need to be carried out in order to improve the interobserver consistency.…”
Section: Discussionmentioning
confidence: 99%
“…MR tumor regression grade (mrTRG) has been reported to be an excellent method for differentiating good from poor response in patients with rectal cancer [ 41 42 ]. Further studies need to be carried out in order to improve the interobserver consistency.…”
Section: Discussionmentioning
confidence: 99%
“…There are multiple ordinal scales in the literature that represent variations or adaptations to it but in general, when T2-WI intermediate “tumour” signal predominates over hypointense fibrosis or clear hyperintense “acellular mucin” (mrTRG4-5, mrTRG5 hardly ever being observed in our experience), a poor response is assumed, and the 3-year disease free survival is 21% inferior compared to favourable mrTRG1-3s [ 23 ]. mrTRG3 may fall on the “good side” regarding long-term outcome [ 26 ] but the likelihood of a pCR or cCR when T2-intermediate clearly “tumoural” signal remains after neoadjuvant treatment is low, and it is therefore considered a sign of an incomplete response [ 27 ]. Significant restriction to diffusion on Diffusion-weighted Imaging (DWI) …”
Section: Re-staging After Neoadjuvant Therapymentioning
confidence: 99%
“…Study characteristics and methodological details are shown in Tables 1 and 2 and Supplemental Tables 4-10 (Supplemental material available online). Combined, 19 studies investigated T2-mrTRG (25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43), 39 studies investigated DW-MRI (25,32,37,, 13 studies investigated PW-MRI (80)(81)(82)(83)(84)(85)(86)(87)(88)(89)(90)(91)(92), and 15 studies investigated endoscopy with or without MRI (26,36,(93)(94)(95)(96)(97)(98)(99)(100)(101)(102)…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…The PPV and NPV of T2-mrTRG grade 1 for detecting ypCR were in the range of 0%-99% and 73%-98%, respectively. The majority of studies (n = 17) were conducted retrospectively (25,(27)(28)(29)(30)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43). Sample sizes were in the range of 41-439 patients.…”
Section: T2-weighted Mrtrg Scoring Systemmentioning
confidence: 99%
See 1 more Smart Citation